THE INFLUENCE OF HEDONIC SHOPPING VALUE, WEB INFORMATIVNESS, WEB ENTERTAINMENT ON E-LOYALTY WITH E-SATISFACTION AS A MEDIATION ON TOKOPEDIA - Nyoman Udayana, Ida Bagus; Ningrum, Nonik Kusuma; Andriani, Ellyta Liska (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This research was conducted with in order to identify and analyze the factors that influence loyalty Tokopedia users of online shopping services. With several related variables in this research are hedonic shopping value, web informativeness, web entertainmnet, e-satisfaction, and e-loyalty as dependent variables. The population of this research is tokopedia users, with a sample of 100 tokopedia users. Data collection was done by using a questionnaire method. The test result in this study are that hedonic shopping value has positive effect on e-satisfation, wen informativeness and web entertainmnet have a positive effect on e-satisfaction, and E-Satisfaction has positive effect on E-Loyalty. Which Means that hypothesis testing is accepted. Keyword : Hedonic Shopping Value; Web Informativeness; Web Entertainmnet; E-Satisfaction; E-Loyalty